Kelayakan Usaha Agrowisata di Kabupaten Rembang - Achmat Bukhori; Rita Nurmalina (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2021)
Agrotourism is tourism that utilizes agricultural business as a tourism destination, with the purpose of recreation, increasing knowledge, and building business in agricultural. The purpose of this research is to analyze the investment feasibility of agrotourism. The location of the research was conducted in De Kampoeng Rembang Agrotuorism which is an agrotourism with the main commodity of dragon fruit and combined with edu-tourism. In this research will be compared to the feasibility business of agrotourism without restaurant facilities (scenario I) with agrotourism that adds restaurant facilities (scenario II). Feasibility of non-financial business was analyzed using the market aspects, technical aspects, management aspects, law aspects, social, economic, cultural aspects, and environmental aspects. Whereas feasibility of financial business was analyzed using the investment criteria, that covered NPV, Net B/C, IRR, and Payback Period, and also switching value analysis. The result shows that De Kampoeng Rembang Agrotourism is feasible based on non-financial aspects and financial aspects. The result of investment criteria analysis shows that the business of agrotourism with restaurant facilities have better performance than the business of agrotourism without restaurant facilities. While based on switching value analysis, the result shows that the decreasing in the number of visitors is more sensitive to business feasibility compared to the increasing in the salary of permanent workers on both scenarios